Copper nanoclusters and preparation method and application thereof

By combining copper nanoclusters with casein ligands with waterborne polyurethane, the problems of flammability and bacterial growth in waterborne polyurethane materials have been solved, resulting in improved flame retardancy, antibacterial properties, and mechanical properties, while simplifying the production process and reducing costs.

CN122278000APending Publication Date: 2026-06-26CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610438207.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-04-03
Publication Date
2026-06-26

Smart Images

  • Figure CN122278000A_ABST
    Figure CN122278000A_ABST
Patent Text Reader

Abstract

This application discloses a copper nanocluster, its preparation method, and its application. The copper nanocluster comprises copper atom aggregates and a stabilizer coated on the surface of the copper atom aggregates; the stabilizer includes casein. The copper nanocluster of this application not only improves the mechanical properties and hydrophobic properties of materials, making waterborne polyurethane materials hydrophobic, but also endows waterborne polyurethane materials with excellent flame-retardant and antibacterial properties. Furthermore, it simplifies the production process, reduces product costs, and the materials used have the advantages of being green and renewable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of nanomaterials, and in particular to a copper nanocluster, its preparation method, and its application. Background Technology

[0002] Waterborne polyurethane (WPU) is widely used in coatings, adhesives, and other fields due to its environmental friendliness, non-toxicity, good flexibility, and abrasion resistance. However, traditional waterborne polyurethane is itself a flammable material with a low limiting oxygen index (LOI), and its combustion process is accompanied by a large amount of dripping, which can easily cause secondary fires. In addition, WPU film surfaces are prone to bacterial and mold growth, limiting its use in medical and health applications, food packaging, and humid and hot environments.

[0003] In existing technologies, waterborne polyurethane is usually given corresponding functions by physically adding inorganic flame retardants, such as aluminum hydroxide and magnesium hydroxide, as well as antibacterial agents, such as silver nanoparticles and antibiotics. However, inorganic flame retardants are usually added in large quantities and are prone to agglomeration, which leads to a significant decrease in the mechanical properties of the material (such as elongation at break and toughness). On the other hand, single antibacterial agents do not have flame retardant properties and have poor compatibility with the matrix, and are prone to precipitation from the material surface, leading to failure.

[0004] Therefore, developing a waterborne polyurethane modified material that can simultaneously achieve high-efficiency flame retardancy, excellent antibacterial properties, and even enhance mechanical properties is a technical problem that urgently needs to be solved in this field. Summary of the Invention

[0005] In view of this, this application provides a copper nanocluster with casein as a ligand, which can be uniformly mixed with waterborne polyurethane material by a simple method, and can be used as a flame retardant and antibacterial additive for waterborne polyurethane material, and can improve the mechanical properties and hydrophobic properties of waterborne polyurethane material.

[0006] This application provides a copper nanocluster, comprising copper atom aggregates and a stabilizer coated on the surface of the copper atom aggregates; The stabilizer includes casein.

[0007] This application also provides a method for preparing copper nanoclusters, including: Copper nanoclusters were obtained by in-situ reduction reaction and dialysis of a mixture of stabilizer, copper salt solution and sodium borohydride.

[0008] In some specific implementations, the mass ratio of the stabilizer, copper salt solution, and sodium borohydride is 1000:(10-30):(5-10). The copper salt solution includes a copper sulfate solution; The in-situ reduction reaction is carried out under conditions of pH 10 to 12.

[0009] In some specific implementations, the temperature of the in-situ reduction reaction is between 10°C and 50°C; The in-situ reduction reaction takes 6 to 12 hours.

[0010] In some specific implementations, the dialysis time is 20 hours to 80 hours; The dialysis bag used in the dialysis has a molecular weight of 10,000 to 100,000; The dialysis process also includes lyophilization.

[0011] This application also provides a composite film comprising, by mass fraction, 2% to 8% of copper nanoclusters as described above and 92% to 98% polyurethane.

[0012] This application also provides a method for preparing a composite thin film, comprising: The copper nanoclusters described above are mixed with polyurethane and molded to obtain a composite film.

[0013] In some specific implementations, the mixing includes stirring and sonication, wherein the stirring time is 20 to 40 minutes and the sonication time is 10 to 20 minutes.

[0014] In some specific implementations, the molding process includes room temperature drying and vacuum drying; The room temperature drying is performed in a polytetrafluoroethylene mold, and the room temperature drying time is 20 hours to 40 hours. The vacuum drying temperature is 40°C to 50°C, and the vacuum drying time is 20 hours to 80 hours.

[0015] This application also provides the use of the composite film as described above in the preparation of flame-retardant, antibacterial packaging materials, coatings or adhesives.

[0016] Casein is rich in amino and hydroxyl groups, which can form hydrogen bonds within the protein, enhancing its mechanical properties. In addition, casein is also a hydrophobic protein that can significantly improve the hydrophobic properties of polyurethane. Its abundant N and P elements can achieve excellent flame retardant effects.

[0017] The copper nanoclusters described in this application can not only improve the mechanical properties and hydrophobic properties of materials, making waterborne polyurethane materials hydrophobic, but also endow waterborne polyurethane materials with excellent flame retardant and antibacterial properties, and can simplify the production process and reduce product costs. The materials used have the advantages of being green and renewable. Attached Figure Description

[0018] Figure 1 This is a schematic diagram of the preparation method of copper nanoclusters provided in Example 1 of this application; Figure 2aThis is a TEM image of the copper nanoclusters provided in Example 1 of this application; Figure 2b This is a STEM image of the copper nanoclusters provided in Example 1 of this application; Figure 2c This is a particle size distribution diagram of the copper nanoclusters provided in Example 1 of this application; Figure 3 Mechanical property test diagrams of composite films with different contents of copper nanoclusters provided in Examples 2-5 and Comparative Example 1 of this application; Figure 4 The smoke production test diagrams are provided for composite films with different contents of copper nanoclusters in Examples 2-5 and Comparative Example 1 of this application. Figure 5 The antibacterial effects of composite films with different contents of copper nanoclusters provided in Examples 2-5 and Comparative Example 1 of this application are illustrated. Figure 6 The antibacterial effect of the composite thin film doped with 8 wt% casein provided in Comparative Example 2 of this application is shown in the figure. Figure 7 The mechanical properties of the composite film provided in Comparative Example 2 of this application are tested with different concentrations of casein. Detailed Implementation

[0019] It should be understood that the expression “one or more of…” individually includes each of the objects described after the expression, as well as various different combinations of two or more of the described objects, unless otherwise understood from the context and usage. The expression “and / or” combined with three or more described objects should be understood to have the same meaning, unless otherwise understood from the context.

[0020] The terms “including,” “having,” or “containing,” including the use of their grammatical synonyms, should generally be understood as open-ended and non-restrictive, for example, not excluding other unstated elements or steps, unless otherwise specifically stated or understood from the context.

[0021] It should be understood that the order of steps or the sequence of actions is not important as long as this application remains operational. Furthermore, two or more steps or actions may be performed simultaneously.

[0022] The use of any and all instances or exemplary language such as “e.g.” or “include” in this document is intended merely to better illustrate the application and does not constitute a limitation on the scope of the application. No language in this specification should be construed as indicating that any unclaimed element is essential to the practice of this application.

[0023] Furthermore, the numerical ranges and parameters used to define this application are approximate values, and the relevant values ​​in the specific embodiments have been presented as precisely as possible. However, any numerical value inevitably contains standard deviations due to individual test methods. Therefore, unless otherwise explicitly stated, it should be understood that all ranges, quantities, values, and percentages used in this disclosure are modified with the word "approximately." Here, "approximately" generally means that the actual value is within plus or minus 10%, 5%, 1%, or 0.5% of a specific value or range.

[0024] The main drawbacks of existing technologies include: 1. Poor compatibility between additives and the matrix, making it difficult to improve functionality and maintain or enhance mechanical properties; 2. Currently, it is difficult for additives to simultaneously improve the flame retardant and antibacterial properties of waterborne polyurethane; 3. Additives are costly and lack green, environmentally friendly, and renewable properties.

[0025] This application provides a copper nanocluster, comprising copper atom aggregates and a stabilizer coated on the surface of the copper atom aggregates; The stabilizer includes casein.

[0026] This application provides a method for preparing copper nanoclusters, including: Copper nanoclusters were obtained by in-situ reduction reaction and dialysis of a mixture of stabilizer, copper salt solution and sodium borohydride.

[0027] This application first dissolves the stabilizer in deionized water, adjusts the pH value, adds a copper salt solution, and stirs to obtain a mixture. In some specific implementations, the mass ratio of the stabilizer to the copper salt solution is 1000:(10-30), preferably 1000:(15-18), and more preferably 1:16. In some specific implementations, after mixing the stabilizer with deionized water, an alkali is added to adjust the pH value to 10 to 12, preferably 11. The alkali includes sodium hydroxide. The mixing of the stabilizer and deionized water includes ultrasonic treatment for 5 to 8 hours, preferably 6 hours. In some specific implementations, the casein is mixed with deionized water to form a casein solution with a concentration of 8 mg / mL to 10 mg / mL, preferably 10 mg / mL. In some specific implementations, the copper salt solution includes, but is not limited to, a copper sulfate solution. In some specific implementations, the concentration of the copper salt solution is 8 mmol / L to 12 mmol / L, preferably 10 mmol / L.

[0028] This application then performs an in-situ reduction reaction and dialysis on the mixture in the presence of sodium borohydride to obtain copper nanoclusters. In some specific implementations, the mass ratio of the stabilizer, copper salt solution, and sodium borohydride is 1000:(10-30):(5-10), preferably 1000:(15-18):(6-8), and more preferably 1:16:5.8. In some specific implementations, the temperature of the in-situ reduction reaction is 10°C to 50°C, preferably 20°C; the time of the in-situ reduction reaction is 6 h to 12 h, preferably 8 h, and the solution changes from light blue to reddish-brown when the reaction is complete. In some specific implementations, the dialysis time is 20 h to 80 h; the molecular weight of the dialysis bag used for dialysis is 10,000 to 100,000, preferably 20,000; and the dialysis is followed by lyophilization. The copper nanoclusters are prepared by in-situ reduction of copper salt using casein as a stabilizer. The purpose of dialysis is to remove heteroatoms and obtain a copper nanocluster solution with casein as a ligand.

[0029] The copper nanoclusters impart excellent mechanical properties to the waterborne polyurethane film, while also giving it flame-retardant and antibacterial properties. The production process is simple, and the waterborne polyurethane matrix used is green and environmentally friendly, while casein is also a renewable green material.

[0030] This application also provides a composite film comprising, by mass fraction, 2% to 8% of copper nanoclusters as described above and 92% to 98% polyurethane.

[0031] The composite film described in this application includes copper nanoclusters. The mass fraction of the copper nanoclusters is 2% to 8%, and can be 2%, 3%, 4%, 5%, 6%, 7%, or 8%, preferably 6%.

[0032] The composite film is a copper nanocluster modified waterborne polyurethane composite film with casein as a ligand. The composite film has a contact bactericidal effect on Escherichia coli, Staphylococcus aureus, and mold.

[0033] This application also provides a method for preparing a composite thin film, comprising: The copper nanoclusters described above are mixed with polyurethane and molded to obtain a composite film.

[0034] This application involves dissolving copper nanoclusters in deionized water, then mixing them with polyurethane and molding them to obtain a composite film. In some specific implementations, 0.7 g to 1 g of the copper nanoclusters is dissolved in 30 mL to 50 mL of deionized water, preferably 0.798 g is dissolved in 40 mL of deionized water. In some specific implementations, the mixing includes stirring and sonication, with the stirring time being 20 min to 40 min, preferably 30 min, and the sonication time being 10 min to 20 min, preferably 15 min.

[0035] In some specific implementations, the molding process includes room temperature drying and vacuum drying; the room temperature drying is performed in a polytetrafluoroethylene mold, and the room temperature drying time is 20h to 40h, preferably 24h; the vacuum drying temperature is 40℃ to 50℃, and the vacuum drying time is 20h to 80h, preferably 48h.

[0036] The method for preparing the composite film includes: 1) synthesizing an aqueous dispersion of copper nanoclusters with casein as a ligand; 2) physically blending the obtained aqueous dispersion of nanoclusters with an aqueous polyurethane dispersion to obtain a modified polyurethane; 3) drying and molding the modified polyurethane through a film-laying process to obtain a polyurethane composite film with flame retardant and antibacterial properties.

[0037] The composite film described in this application includes polyurethane. In some specific implementations, the polyurethane includes waterborne polyurethane. Waterborne polyurethane materials have been widely used in packaging, coating, and crosslinking agents due to their excellent properties. However, waterborne polyurethane materials have many problems during use, such as flammability and susceptibility to bacterial and fungal attacks. Current research shows that single additives cannot adequately address the three aspects of flame retardancy, antibacterial properties, and enhanced mechanical properties. Many additives suffer from poor compatibility with the waterborne polyurethane matrix, leading to a decrease in mechanical properties. This application not only solves the problem of additives causing a decrease in the mechanical properties of the matrix material but also simultaneously endows the waterborne polyurethane material with flame retardant and antibacterial functions, greatly reducing the problems of flammability and susceptibility to bacterial and fungal attacks encountered by waterborne polyurethane during use. This application features a simple production process, low cost, and good performance, achieving a triple improvement in polyurethane matrix materials.

[0038] This application also provides the use of the above-described composite material in the preparation of flame-retardant, antibacterial packaging materials, coatings, or adhesives.

[0039] The present application is further illustrated below with reference to embodiments. The scope of protection of the present application is not limited to the following embodiments.

[0040] Example 1

[0041] This embodiment provides a copper nanocluster, the preparation method of which includes: See Figure 1 , Figure 1The diagram below illustrates the preparation method of copper nanoclusters provided in Example 1. 1g of casein was weighed and dissolved in 100mL of alkaline aqueous solution. The solution was sonicated for 6 hours to completely dissolve, yielding a 10mg / mL casein solution. The pH was adjusted to 11, and 10mL of 10 mmol / L copper sulfate solution was added. After coordination for 10 minutes, 10mL of freshly prepared 20 mmol / L sodium borohydride solution was added to reduce copper ions. The mixture was stirred at a constant temperature of 20°C for 8 hours, during which the solution changed from light blue to reddish-brown. Dialysis was performed for two days using a dialysis bag with a molecular weight of 20,000, changing the water every 4 hours to remove small molecules within the nanoclusters. Finally, a pure aqueous solution of copper nanoclusters with casein as the ligand was obtained. After lyophilization, copper nanoclusters with casein as the ligand (CuNCs@Casein) were obtained.

[0042] Figure 2a This is a TEM image of the copper nanoclusters provided in Example 1 of this application; Figure 2b This is a STEM image of the copper nanoclusters provided in Example 1 of this application; Figure 2c This is a particle size distribution diagram of the copper nanoclusters provided in Example 1 of this application.

[0043] Example 2

[0044] This embodiment provides a composite film (WPU-6%), the preparation method of which includes: 1. Take 0.798 g of the copper nanocluster sample prepared in Example 1, dissolve it in 40 mL of deionized water and add it to 25 mL of aqueous polyurethane emulsion to obtain a nanocluster solid content of 6% of the total solid content.

[0045] 2. Stir mechanically for 30 minutes to fully mix and uniformly disperse the nanoclusters with the waterborne polyurethane, then sonicate for 15 minutes to remove air bubbles from the dispersion, or remove air bubbles by vacuuming for 15 minutes.

[0046] 3. Pour the mixed emulsion into a polytetrafluoroethylene mold, place it in an oven, and dry at 40-50℃ for 48 hours to obtain a composite film with a uniformly dispersed loading of 6%.

[0047] Example 3

[0048] This embodiment provides a composite film (WPU-2%), which differs from Embodiment 2 only in that the copper nanocluster content in the composite film is 2%.

[0049] Example 4

[0050] This embodiment provides a composite film (WPU-4%), which differs from Embodiment 2 only in that the copper nanocluster content in the composite film is 4%.

[0051] Example 5

[0052] This embodiment provides a composite film (WPU-8%), which differs from Embodiment 2 only in that the copper nanocluster content in the composite film is 8%.

[0053] Comparative Example 1

[0054] This comparative example provides a composite film that is a pure WPU film without any modifiers, which is formed by directly drying the aqueous polyurethane emulsion as a blank control (WPU-0%).

[0055] Comparative Example 2

[0056] This comparative example provides a composite film that is a physically mixed casein film. Unmodified casein powder is directly dissolved and added to WPU emulsion (content 8 wt.%) without introducing a copper source to prepare the composite film.

[0057] Comparative Example 3

[0058] This comparative example provides a physically mixed composite film, prepared by directly dissolving unmodified casein powder and adding it to a WPU emulsion (content 6 wt.%) without introducing a copper source. Performance tests were conducted on the composite films provided in Examples 2-6 and Comparative Examples 1-3 using the following methods: Mechanical properties: The composite film was cut into 2mm pieces. Dumbbell-shaped films with a diameter of 12 mm were subjected to tensile testing at a speed of 50 mm / min on a tensile testing machine to obtain stress-strain curves, according to standard GB / T 1040.1-2006; the mechanical property test graphs of composite films with different contents of copper nanoclusters provided in Examples 2-5 and Comparative Example 1 are shown below. Figure 3 As shown; Figure 7 Mechanical property test diagrams of the composite film provided for this comparative example with different concentrations of casein doping; Antibacterial properties: A volume of the composite film of the same size was placed in bacterial culture medium and cultured together for 15 hours. After culturing, the bacterial solution was diluted, and 100 μL was evenly spread onto a broth solid culture medium. The medium was then placed in a 37°C incubator for 12 hours. The bacterial count was then photographed and recorded. The antibacterial effects of the composite films with different copper nanocluster contents provided in Examples 2-5 and Comparative Example 1 are shown in the figures. Figure 5 As shown. Figure 6 The antibacterial effect of the composite film doped with 8 wt% casein provided for this comparative example is shown in the figure.

[0059] Smoke production test: Prepare 100mm A 100mm thick, smooth-surfaced water-based polyurethane composite film, 6-50mm thick, is wrapped with 0.03mm aluminum foil on the back and four sides, leaving 100mm of exposed surface. A 100mm thick film was conditioned at (23±5) ℃ and (50±20)%RH for ≥16 h, then sealed for testing. It was placed in a cone calorimeter, and the spark igniter was turned on to collect smoke production data. The smoke production test graphs for composite films with different copper nanocluster contents provided in Examples 2-5 and Comparative Example 1 are shown below. Figure 4 As shown.

[0060] The test results are shown in Table 1.

[0061] Table 1

[0062] As shown in Table 1 and the attached figures: Flame retardant performance: Compared to Comparative Example 1 (LOI 19.2%), the LOI of Example 2 increased to 21.68%, and the cone calorimetry test showed that the total smoke release (TSP) decreased by about 70%. This indicates that the addition of copper nanoclusters with casein as a ligand plays a highly efficient role in flame retardancy and smoke suppression, overcoming the problems of low flame retardancy and high smoke concentration during combustion of waterborne polyurethane materials. Mechanical properties: By introducing CuNCs@Casein, this application not only improved the tensile strength (from 18.1 MPa to 25.3 MPa) but also improved the elongation at break (from 1100% to 1300%), achieving "reinforcement and toughening". This is attributed to the strong interaction and nano-size effect formed between the nanoclusters and polyurethane segments. Antibacterial properties: The inhibition rates of Escherichia coli and Staphylococcus aureus in Examples 2 and 5 both exceeded 90.0%, demonstrating that the copper nanoclusters release copper ions and other active substances with excellent bactericidal ability and can effectively inhibit bacterial growth. The above description is merely a preferred embodiment of this application, but the scope of protection of this application is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in this application, based on the technical solution and application concept of this application, should be included within the scope of protection of this application.

Claims

1. A copper nanocluster, characterized in that, Including copper atom aggregates and stabilizers coating the surface of the copper atom aggregates; The stabilizer includes casein.

2. A method for preparing copper nanoclusters, characterized in that, include: Copper nanoclusters were obtained by in-situ reduction reaction and dialysis of a mixture of stabilizer, copper salt solution and sodium borohydride.

3. The preparation method according to claim 2, characterized in that, The mass ratio of the stabilizer, copper salt solution and sodium borohydride is 1000:(10-30):(5-10). The copper salt solution includes a copper sulfate solution; The in-situ reduction reaction is carried out under conditions of pH 10 to 12.

4. The preparation method according to claim 2, characterized in that, The temperature of the in-situ reduction reaction is 10°C to 50°C; The in-situ reduction reaction takes 6 to 12 hours.

5. The preparation method according to claim 2, characterized in that, The dialysis time is 20 hours to 80 hours; The dialysis bag used in the dialysis has a molecular weight of 10,000 to 100,000; The dialysis process also includes lyophilization.

6. A composite film, characterized in that, It comprises 2% to 8% copper nanoclusters as described in claim 1 and 92% to 98% polyurethane by mass fraction.

7. A method for preparing a composite thin film, characterized in that, include: The copper nanoclusters as described in claim 1 are mixed and molded with polyurethane to obtain a composite film.

8. The preparation method according to claim 7, characterized in that, The mixing includes stirring and sonication, with the stirring time being 20 to 40 minutes and the sonication time being 10 to 20 minutes.

9. The preparation method according to claim 7, characterized in that, The molding process includes room temperature drying and vacuum drying; The room temperature drying is performed in a polytetrafluoroethylene mold, and the room temperature drying time is 20 hours to 40 hours. The vacuum drying temperature is 40°C to 50°C, and the vacuum drying time is 20 hours to 80 hours.

10. The use of the composite film as described in claim 6 in the preparation of flame-retardant, antibacterial packaging materials, coatings or adhesives.